Development of Interactive Learning Media for A1 Vocabulary on the Theme “Freizeit” Using the Genially Website at Universitas Negeri Medan (Lembaga Pengembangan Kinerja Dosen, 2025)
In this study, an interactive learning medium was developed to practice German A1-level vocabulary with the theme “Freizeit”, based on a website created using Genially. This research is classified as development research, in which the development process of the learning medium employed the ADDIE model, consisting of five stages: analysis, design, development, implementation, and evaluation. The study was conducted in the German Language Education Study Program at Universitas Negeri Medan. The research data consisted of vocabulary on the theme “Freizeit”, taken from the Netzwerk textbook and other online sources. The research subjects were second-semester students of the 2024 cohort. The instruments used included questionnaires, pretest and posttest, expert validation sheets, and documentation. The results of the validation from media experts and material experts indicated that the medium was suitable for use in learning, with scores of 92% and 89%, respectively. The trial conducted with students showed a positive response with an average score of 91%. The students’ average pretest score was 58.3, which increased to 84.7 in the posttest. Statistical tests revealed that the calculated t-value (12.45) was greater than the critical t-table value (2.045), indicating a significant difference between the pretest and posttest results. Thus, the use of the Genially interactive learning medium proved effective in improving German A1 vocabulary mastery and was able to create a more engaging and interactive learning atmosphere while supporting independent learning.